Fetal Tele-Echocardiography—An Approach to Improving Diagnosis and Management - Badreldeen Ahmed; Amal Elsisi; Justin C. Konje (Diagnostics)
Introduction: Antenatal diagnosis of cardiac abnormalities and counselling parents about postnatal care require a multidisciplinary team, which includes a paediatric cardiologist, a neonatologist, and a fetal medicine physician. Some of these kinds of expertise are not available in all centres with fetal medicine expertise. However, with modern technology, this could be provided remotely. Our objective was to assess the feasibility and outcomes of prenatal multidisciplinary tele-echocardiography diagnostic and counselling services. Materials and Methods: Two centres based in separate countries provided a joint diagnostic and counselling service over a period of 14 months. The primary centre performed the fetal echocardiography with a Voluson E10 machine, and images were transmitted live using Zoom OPS system with video-consultation and counselling. The fetal echo was performed using the ISUOG Guidelines check list. Results: There was an initial feasibility period of 2 months during which 10 women whose fetuses had normal hearts were scanned to test the workability of the system. Over a period of 12 months, 513 high-risk fetuses were then scanned, and out of these, 27 had congenital malformations. The most common were hypoplastic left heart syndrome (HHLS) and atrio-ventricular septal defect. Tele-echocardiography and counselling were successful in all the cases. Satisfaction with the service was 3.8/4, with the main limitation being the need for further referral to a tertiary centre for delivery. Conclusions: Tele-echocardiography is reliable, and when combined with live counselling and support from a paediatric cardiologist, it is an option acceptable to patients. The greatest benefit was from being counselled by a team of experts at a single consultation rather than having to travel to another centre for consultation. With rapidly evolving technology, making video transmission easier and less expensive, we feel that consideration should be given not only to the development of tele-echocardiography but also to extending it to other aspects of fetal medicine.